Single‐Cell Quantification of Triple‐AAV Vector Genomes Coexpressed in Neurons. Issue 5 (26th May 2022) - Maturana, Carola J.; Verpeut, Jessica L.; Engel, Esteban A.
Abstract: Adeno‐associated viruses (AAVs) are one of the most widely used types of viral vectors for research and gene therapy. AAV vectors are safe, have a low immunogenic profile, and provide efficient and long‐term transgene expression in a variety of tissues and organs targeted by a specific serotype. Despite these unique features, therapeutic applications, as well as basic research studies, of AAVs have been limited by their packaging capacity of less than 5 kb. Multiple strategies have been explored to deliver large genes. One strategy is to split large transgenes into two or three fragments and package them into separate AAV capsids, generating dual or triple AAV vectors. Combining the fragments potentially allows reconstitution of an mRNA transcript containing the complete sequence of transgene in the same cell. The success of AAVs as vectors for the delivery of large or multiple genes depends directly on the efficiency of co‐transduction. Here, we describe a method to measure the efficacy of codelivery, quantifying the number of AAV vectors per cell. We detail how to calculate the average number of incoming AAV genomes in neurons, given the distribution of cell fluorescence across in vitro and in vivo experimental models. To validate the method, we simulated a triple AAV strategy using three fluorescent‐protein‐encoding genes. We provide a general protocol for constructing plasmids and producing and purifying AAV vectors. We also include a protocol for triple AAV vector co‐transduction in primary neuronal cultures and mouse brain. The method can be applied to multiple organs and tissues for the treatment of disorders caused by mutations in multiple or large genes. These protocols will be useful for researchers working to develop and improve new gene delivery technologies. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Construction of AAV plasmids and production of AAVs Basic Protocol 2 : AAV transduction of primary superior cervical ganglia (SCG) neuronal cultures Basic Protocol 3 : Mouse surgery, AAV injection, and tissue collection and processing Basic Protocol 4 : Image analysis and AAV genome quantification